Insight into the factors of mountain bog and forest development in the Schwarzwald Mts.: Implications for ecological restoration. (July 2022) - Gałka, Mariusz; Hölzer, Adam; Feurdean, Angelica; Loisel, Julie; Teickner, Henning; Diaconu, Andrei-Cosmin; Szal, Marta; Broder, Tanja; Knorr, Klaus-Holger
Graphical abstract: Highlights: Multi-proxy study on the long-term development of mountain bog and forest in Central Europe. Self-recovery of the peat formation process began at ca. 200 cal BP. The impact of dust deposition led to changes in local plant succession. Shallow water table depths (<10 cm below the surface) may not be necessary for restoration efforts. Fagus sylvatica was replaced by Picea abies and Pinus sylvestris during the last two centuries. Abstract: Peatlands are a significant landscape component in temperate mountain ranges and serve multiple functions. However, many peatlands were damaged, altered, or drained over the past centuries, and knowledge about their development is needed for their protection and sustainable management. In our study, we analysed two peat cores from a bog site located in the Black Forest (Southwest Germany) using high-resolution multi-proxy palaeoecological analysis, including biological indicators (plant macrofossils, pollen, testate amoebae), macro-and micro-charcoal as well as geochemical analyses (peat stoichiometry and stable isotopes (δ 13 C, δ 15 N)) supported by radiocarbon dating. We tracked the development of the peatland and forest ecosystem to (i) determine their current ecological state, and to (ii) assess the role of different agents of change at the catchment scale on peatland development. The overall objective was to determine natural reference conditions as a basis for the restoration of degraded mountain bogs in the Black Forest Mountains and other temperate mountain ranges. Our results revealed that: i) the bog developed on mineral bedrock of slight slope through paludification around ca. 10, 000 cal. BP; ii) the pristine plant populations dominated by Sphagnum fuscum occurring from 6200 cal. BP were replaced by Sphagnum medium/divinum and Eriophorum vaginatum since ca. 3300 cal. BP, most likely due to hydrological disturbances and possible dust deposition on the bog; iii) peat formation at the study site seems still active despite relatively deep water levels (ca. 22–26 cm below surface) and was active over the last 8000 years also when WTD varied between 12 and 26 cm; iv) the self-recovery of peat formation at this mountain bog is possible; v) the protection and restoration of mountain bog ecosystems should also consider land cover changes in the surrounding catchment, serving as further indicators or drivers of mountain bog development.